The Africa Competitiveness Report 2015 - World Economic Forum; World Bank; African Development Bank; Organisation for Economic Co-operation and Development (Geneva: World Economic Forum, 2015)
The Africa Competitiveness Report 2015 comes out at a promising time for the continent: for 15 years growth rates have averaged over 5 percent, and rapid population growth holds the promise of a large emerging consumer market as well as an unprecedented labor force that - if leveraged - can provide significant growth opportunities. Moreover, the expansion of innovative business models, such as mobile technology services, is indicative of the continents growth potential. However, Africa continues to be largely agrarian, with an economy that is underpinned by resource-driven growth and a large and expanding informal sector. Indeed, more than a decade of consistently high growth rates have not yet trickled down to significant parts of the population: nearly one out of two Africans continue to live in extreme poverty, and income inequality in the region remains among the highest in the world. What is more, across sectors - from agriculture to manufacturing and services - productivity levels remain low. It will be necessary to raise productivity across all sectors of the economy to achieve higher growth and create quality employment, and turn this progress into sustainable inclusive growth.